Ketahanan Pangan Sebelum dan Selama Pandemi Covid-19 di Kabupaten Bandung - Muthiah Syakirotin; Tuti Karyani; Trisna Insan Noor (Jurnal Ilmu Pertanian Indonesia, 2022)
The World Food Programme said that in 2020 there were 768 million people who experienced chronic hunger due to the increase in world poverty during the Covid-19 pandemic. In facing the spread of Covid-19, the agricultural sector is a priority because it is directly related to national food security. As a national food barn, West Java is affected by the increase in poor people. Pada in 2021, Bandung Regency experienced extreme poverty, which is 2.64%; this will affect food security in particular, in terms of affordability. Therefore, the availability of accurate and fast food security information is needed to prevent and handle food insecurity in order to provide direction and recommendations for preparing programs and policies, especially during the Covid-19 pandemic. This study was based on analyzing differences in food security before and during the Covid-19 Pandemic in Bandung Regency regarding food availability, affordability, and utilization. The analysis used a descriptive quantitative method with a paired sample t-test. The data source is secondary data from the Food Security and Vulnerability Atlas report of Bandung Regency. The analysis shows a noticeable difference between the food security of Bandung Regency before and during the Covid-19 pandemic, namely the decrease in the composite value of food security, especially in affordability. The most significant average increase occurred in the lowest welfare ratio indicator in 2020. Keywords: food security, Covid-19